1,3,4-Oxadiazole derivatives as potent antifungal agents: Synthesis, biological evaluation and an in silico study - Quy Nguyen; Cuong Quoc Nguyen; Quang De Tran; Dang Quang Le; Thi Buu Hue Bui (CTU Journal of Innovation and Sustainable Development)
Ten 1,3,4-oxadiazole derivatives were prepared and evaluated for their anti-fungal activities. The results showed that compounds 4a, 7a, and 7f displayed activity against F. oxysporum. Molecular docking study indicated that compounds 4a, 7a, and 7f exhibited affinity towards F. oxysporum’s β-tubulin by showing low binding energies as well as interactions with the key amino acids in the binding sites of the receptor.